Fairness for Creditors in Bankruptcy Proceedings: Between Certainty and Economic Interests - Imam Nurhadi; Huzaimah Al-Anshori; Ali Huristak Hartawan Hasibuan (Journal of Law, Politic and Humanities, 2026)
This study aims to analyze the concept of creditor justice in bankruptcy proceedings in Indonesia, with a particular focus on the tension between legal certainty and economic interests. Bankruptcy, as a legal mechanism for debt settlement, often places creditors in an unequal position, especially in relation to the different classifications of creditors, namely secured creditors, preferred creditors, and unsecured creditors. This research employs a normative juridical method with statutory and conceptual approaches, referring to Law No. 37 of 2004 and relevant legal literature on bankruptcy and suspension of debt payment obligations (PKPU). The findings indicate that although the Indonesian bankruptcy system provides legal certainty through clear, structured, and relatively fast procedures, substantive justice for all creditors has not been fully achieved. This is reflected in the unequal distribution of bankruptcy assets, where unsecured creditors often occupy the most disadvantaged position. In addition, the PKPU mechanism, which is intended as a debt restructuring tool, also faces practical challenges, including the potential misuse by debtors acting in bad faith. These conditions demonstrate that the bankruptcy system still encounters difficulties in balancing legal certainty with economic fairness. Therefore, regulatory strengthening and improved supervision are required to create a more balanced, fair, and effective system that better protects the interests of all parties, particularly creditors.